Infrared Thermal Imaging of Ocular Surface Temperature Associated with Peripartum Buffaloes (Bubalus bubalis) - Allu, Teja; Sakthivel, Jeyakumar; Kumaresan, Arumugam; Puttaiah Ramesha, Kerekoppa; Sivaram, Muniandy; Amritrao Kataktalware, Mukund; Nitai Das, Dayal (The Indian Journal of Animal Reproduction, 2025)
The potentiality of digital infrared thermal (IRT) imaging technology has been explored for the first time to monitor the temperature variation during pre, peri and post-partum stages of parturition in buffaloes. Thermograms were recorded in buffaloes from 96 hours before expected time of calving and continued till 96 hours post-calving with an interval of every six hours. With a ΔT of 0.56°C in the ocular region, the data showed a considerable drop in temperature from 48 hours before the onset of calving. Likewise, the residual temperature showed a comparable and noteworthy downward tendency, suggesting that the circadian rhythm had little effect on the body’s surface temperature. The reduction in temperature is attributed to the progesterone that reduces vascular perfusion and cutaneous circulation. Our study’s findings suggested that ocular surface temperature variation in connection to calving, as monitored by digital infrared thermal imaging could be explored as a promising tool for prediction of the onset of calving process in buffaloes.